The Relationship Among Reading Related Language Learning Strategy and Reading Attitude toward Reading Comprehension Achievement to Fourth Semester Students Of English Education Study Program of PGRI University of Palembang - Marleni Marleni (Universitas PGRI Palembang, 2015)
Abstract This study was aimed at finding out (1) the reading strategies employed and frequent reading strategy employed by the fourth semester students of FKIP PGRI University Palembang in reading English texts, (2) Whether or not there was significant correlation between students’ reading strategies and reading comprehension achievement, and reading attitude and their reading comprehension achievement (3)in what extent the contribution of the students reading strategies and reading attitude toward students’ reading comprehension achievement. The data was collected by distributing two sets of questionnaire sheets and testing a reading comprehension test for 170 students. Pearson Product Moment Coefficients Correlation and Regression Analysis were used to find out whether or not there were significant relationship of students’ reading strategies and reading attitude toward reading comprehension achievement of the fourth semester students’ of English Education study program of PGRI University Palembang as well as their contribution. The finding of this study showed that: first, placing in a word in context was the most frequent strategy used by the students. Second, both students reading strategies and reading attitude had very weak correlation to their reading comprehension achievement. The last students’ reading strategies and reading attitude only had very small contribution to their reading comprehension achievement.The Key Words: Students’ reading related language learning strategies, students reading attitude, and students’ reading achievement.